Synthesis of dietetic structures lipids from spent coffee grounds crude oil catalyzed by commercial immobilized lipases and immobilized Rhizopus oryzae lipase on biochar and hybrid support - Mota, Danyelle A. (2021)
The aim of this study was the valorization of coffee industry residues, namely spent coffee grounds (SCG) as a source of oil, and silverskin (CS) as a source of both oil and biomass, under the concept of the circular economy. Therefore, crude oil from SCG was used to produce low-calorie structured lipids (SL) for food and pharmaceutical industries, and CS to produce biochar by pyrolysis for biotechnological uses. SL were obtained by acidolysis with caprylic or capric acid, or interesterification with ethyl caprylate or ethyl caprate, in solvent-free media, catalyzed by immobilized sn-1,3 regioselective lipases. Silverskin biochar (BIO) was directly used as enzyme carrier or to produce hybrid organic-silica (HB) supports for enzyme immobilization. Rhizopus oryzae lipase (ROL) immobilized on Amberlite (AMB), silica (SIL), BIO or HB, and the commercial immobilized Thermomyces lanuginosus (Lipozyme TL IM) and Rhizomucor miehei (Lipozyme RM IM) lipases were tested. Lipozyme RM IM showed better results in SL production than Lipozyme TLIM or ROL on BIO, SIL or HB. About 90% triacylglycerol conversion was attained after 7 h acidolysis or interesterification. Lipozyme RM IM was more stable in interesterification (80% and 65% activity with ethyl caprylate or ethyl caprate) than in acidolysis (first-order decay) after 10 reuses